Double delay alternating with nutation for tailored excitation facilitates banding‐free isotropic high‐resolution intracranial vessel wall imaging. (2nd June 2021) - Coolen, Bram F.; Schoormans, Jasper; Gilbert, Guillaume; Kooreman, Ernst S.; de Winter, Naomi; Viessmann, Olivia; Zwanenburg, Jaco J. M.; Majoie, Charles B. L. M.; Strijkers, Gustav J.; Nederveen, Aart J.; Siero, Jeroen C. W.
Abstract : The purpose of this study was to evaluate the use of a double delay alternating with nutation for tailored excitation (D‐DANTE)‐prepared sequence for banding‐free isotropic high‐resolution intracranial vessel wall imaging (IC‐VWI) and to compare its performance with regular DANTE in terms of signal‐to‐noise ratio (SNR) as well as cerebrospinal fluid (CSF) and blood suppression efficiency. To this end, a D‐DANTE–prepared 3D turbo spin echo sequence was implemented by interleaving two separate DANTE pulse trains with different RF phase‐cycling schemes, but keeping all other DANTE parameters unchanged, including the total number of pulses and total preparation time. This achieved a reduction of the banding distance compared with regular DANTE enabling banding‐free imaging up to higher resolutions. Bloch simulations assuming static vessel wall and flowing CSF spins were performed to compare DANTE and D‐DANTE in terms of SNR and vessel wall/CSF contrast. Similar image quality measures were assessed from measurements on 13 healthy middle‐aged volunteers. Both simulation and in vivo results showed that D‐DANTE had only slightly lower vessel wall/CSF and vessel wall/blood contrast‐to‐noise ratio values compared with regular DANTE, which originated from a 10%–15% reduction in vessel wall SNR but not from reduced CSF or blood suppression efficiency. As anticipated, IC‐VWI acquisitions showed that D‐DANTE can successfully remove banding artifacts compared with regular DANTE with equal scan time or DANTE preparation length. Moreover, application was demonstrated in a patient with an intracranial aneurysm, indicating improved robustness to slow flow artifacts compared with clinically available 3D turbo spin echo scans. In conclusion, D‐DANTE provides banding artifact‐free IC‐VWI up to higher isotropic resolutions compared with regular DANTE. This allows for a more flexible choice of DANTE preparation parameters in high‐resolution IC‐VWI protocols. Abstract : An alternative to DANTE‐prepared 3D TSE intracranial vessel wall imaging (IC‐VWI) is presented, called Double DANTE (D‐DANTE). We show that D‐DANTE allows for banding‐free IC‐VWI up to higher resolutions compared with regular DANTE with an equal number of DANTE pulses and preparation length. We additionally assessed the influence of D‐DANTE on SNR and flow‐suppression efficiency.